The Effect of Triple Elimination Health Education to Knowledge and Intention Level of Pregnant Women in Screening Triple Elimination Implementation - Ni Nyoman Wiantini; Luh Putu Widiastini; Ni Made Risna (Jurnal Kesehatan Pasak Bumi Kalimantan, 2022)
Human Immuno Deficiency Virus (HIV), hepatitis B and syphilis are very likely to be experienced by mothers during pregnancy and have the potential to cause disability or death. Although there has been an increase in the scope of the implementation of HIV and Hepatitis B screening for pregnant women in Indonesia, there are still cases of pregnant women detected positive for both diseases. This study aims to analyze the effect of triple elimination health education on the level of knowledge and intention of pregnant mothers in the implementation of triple elimination screening. This research is a type of quantitative research with one group pre-post test design method involved 47 respondents of first trimester pregnant women who were selected used purposive sampling technique. The research instrument used was a questionnaire filled out by respondents before and after the triple elimination health education was carried out. The results of the Wilcoxon test analysis showed that there was an effect of triple elimination health education on the level of knowledge and intentions of pregnant women in the implementation of triple elimination screening with p-values of 0.000 and 0.001 (<0.05), respectively. The conclusion of this study is that there is an effect of triple elimination health education on the level of knowledge and intentions of pregnant women in the implementation of triple elimination screening. It is expected that midwives in hospitals need to enhance the knowledge and practice of midwives in the delivery of obstetric health knowledge so that pregnant women can maximize the use of antenatal care services by professional health workers.